Control of arterial hypertension and risk of new-onset of atrial fibrillation in patients with metabolic syndrome - Jani, Ylber; Haxhirexha, Kastriot; Haxhirexha, Ferizat; Pocesta, Bekim; Rexhepi, Atila; Ferati, Fatmir; Kamberi, Ahmet; Zeqiri, Agim; Xhunga, Sotiraq; Serani, Artur; Zylbeari, Lutfi (Journal of Cardiology and Cardiovascular Medicine, 2022)
Background: An association between Atrial Fibrillation (AF) and Metabolic Syndrome (MS) a constellation of abnormalities (high blood pressure, hyperglycemia, dyslipidemia, and abdominal obesity), has been demonstrated. There have been many studies that have shown that elevated blood pressure (BP), was significantly associated with an increased risk of AF. It is uncertain whether maintaining the optimal BP levels can prevent AF in the patients with MS categorized as ‘high-risk’ patients. Objective: The aim of this study was to evaluate the influence of control of BP on the occurrence of new-onset atrial fibrillation in patients with Metabolic Syndrome. Methods: Into this observational study, was enrolled 435 consecutive patients (210 males and 225 females) aged 45-79 years who fulfilled criteria for MS. Participants were selected among primary and secondary care patients, who were receiving ongoing care for arterial hypertension in the period from November 2018 till November 2021. The study was conducted at outpatients in 5 Health Care Clinics (3 Secondary Health Care Clinics and 2 Primary Health Clinics). Patient were categorized according to their BP levels as Group 1-patients with controlled BP, {(patients aged < 65 years Systolic Blood Pressure (SBP) of 120 - 130 mmHg, patients aged ≥ 65 years SBP of 130 - 139 mmHg)} and Diastolic Blood Pressure (DBP), {(patients aged < 65 years of < 80 mmHg. but not < 70 mmHg; patients aged ≥ 65 years of 85 - 89 mmHg)}, or Group 2-patients with uncontrolled BP(> 130/80 mmHg),and in patients aged ≥ 65 years BP (≥ 140/90 mmHg ). Results: New-onset of AF, was more frequent in participants with uncontrolled BP, respectively (34.7% vs. 19.5%, p = 0.009).Patients with uncontrolled BP have more frequent persistent AF (15.2% vs. 0.04%) and permanent AF (0.08% vs. 0.02%), whereas there was not significant changes between groups in relation to frequency of paroxysmal AF, respectively (12.8% vs. 10.9%, p = 0.29). There was observed significant association of uncontrolled BP with: increased frequency of AF (OR = 2.193; 95% CI 1.390 - 3.439), persistent AF (OR = 3.931; 95% CI 1.771 - 8.084), permanent AF (OR = 4.138; 95% CI 1.383-12.381), LA. Dimension ≥ 2.2 cm/m2 (OR = 2.089, 95% CI 1.330 - 3.252), BMI (OR = 5.226, 95% CI 3.155 - 8.659) and 5-risk factors for MS, respectively (OR = 2.998, 95% CI 1.833 - 4.901). Conclusion: Optimal BP levels, can reduce the frequency of new-onset AF in patients with MS categorized as ‘high-risk’ patients. Uncontrolled BP was associated with an increased risk of both subtypes of AF (persistent and permanent) in the patients with MS categorized as ‘high-risk’ patients.